Single molecular switches: Electrochemical gating of a single anthraquinone-based norbornylogous bridge molecule - Darwish, Nadim; Díez-Pérez, I.; Guo, S.; Tao, N.; Gooding, J.; Paddon-Row, M. (American Chemical Society, 2012)
Herein we report the electrochemical gating of a single anthraquinone-based molecule bridged between two gold electrodes using the STM break-junction technique. Once a molecule is trapped between the STM gold tip and the gold substrate, the potential is swept in order to alternate between the oxidized anthraquinone (AQ) and the reduced hydroanthraquinone (H 2AQ) forms. It is shown that the conductance increases about an order of magnitude with a net conversion from the oxidized AQ form to the reduced H 2AQ form. The results obtained from sweeping the potential (dynamic approach) on a single molecule are compared to those obtained from measuring the conductance at several fixed potentials (static approach). By comparing the static and dynamic approach, qualitative information about the kinetics of the redox conversion was achieved. The threshold potential of the conductance enhancement was found to shift to more negative potentials when the potential is swept at a single molecule. This shift is attributed to a slow redox conversion between the AQ and the H 2AQ forms. The hypothesis, of slow redox kinetics being responsible for the observed differences in the single-molecule conductance studies, was supported by electron transfer kinetics studies of bulk self-assembled monolayers using both cyclic voltammetry at different sweeping rates and electrochemical impedance spectroscopy.